Conclusion of An Employment Contract During Remote Work - Natalia RAKSHA; Anna BORENSTEIN; Elena POZDNYAKOVA; Yulia VETCHINOVA; Sergey LIKHACHEV (Communications of International Proceedings, 2021)
In March 2020 the World Health Organization announced that the situation with the spread of a disease caused by a new type of coronavirus could be considered a pandemic. A pandemic is an epidemic spreading across countries and continents, i.e. the highest degree of development of an epidemic process. Restrictions imposed in our country have deprived a significant part of workers of the opportunity to perform their work duties on the premises of the employer. This situation has necessitated the search for other options of interaction between the employer and the employee. One of them has become the temporary transitioning of a part or the whole staff of the company to remote work (Kossov I.A., 2020). The article 312.1 of the Labor Code of the Russian Federation defines remote work as performance by an employee of a labor function defined by a labor contract outside the location of the employer (branch, representative office, other separate structural unit, including located in another area) outside a fixed workplace, territory or facility, directly or indirectly under the control of the employer, subject to the use to perform the labor function and to implement interaction between the employer and the employee on issues related to working process using information and telecommunication systems, i.e. the Internet. Persons who have concluded such a contract on remote work are referred to as remote workers. Remote workers are subject to labor legislation and other normative legal acts containing norms of labor law. However, the legal regulation of their labor is characterized by a number of peculiarities, established by Chapter 49.1 of the Labor Code of the Russian Federation. Some of these peculiarities are directly related to the documentation of the labor relations between the employer and the employee. The Labor Code of the Russian Federation regulates in sufficient detail the hiring for remote work. However, the cases and procedure for registration of transitioning to such work are not clearly defined by the law. Despite the current legal situation, the possibility of temporary transition of employees to remote work still exists.
Keywords: Employment Contract; Employee; Employer; Remote Work; The Internet; Parties.